2013
DOI: 10.1073/pnas.1310914110
|View full text |Cite
|
Sign up to set email alerts
|

Rates and patterns of great ape retrotransposition

Abstract: We analyzed 83 fully sequenced great ape genomes for mobile element insertions, predicting a total of 49,452 fixed and polymorphic Alu and long interspersed element 1 (L1) insertions not present in the human reference assembly and assigning each retrotransposition event to a different time point during great ape evolution. We used these homoplasy-free markers to construct a mobile element insertions-based phylogeny of humans and great apes and demonstrate their differential power to discern ape subspecies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 46 publications
5
67
1
Order By: Relevance
“…2a). During primate evolution, the rate of Alu retrotransposition was 15-fold higher in human, chimpanzee and bonobo lineages than in gorilla and orangutan lineages 77 . Interestingly, LINE1 activity rates were suppressed in the human lineage compared with chimpanzee and bonobo lineages 77,78 , which may have resulted in a less diverse human population compared to non-human primate populations.…”
Section: Box 1 | Evolutionary Impact Of Mobile Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…2a). During primate evolution, the rate of Alu retrotransposition was 15-fold higher in human, chimpanzee and bonobo lineages than in gorilla and orangutan lineages 77 . Interestingly, LINE1 activity rates were suppressed in the human lineage compared with chimpanzee and bonobo lineages 77,78 , which may have resulted in a less diverse human population compared to non-human primate populations.…”
Section: Box 1 | Evolutionary Impact Of Mobile Elementsmentioning
confidence: 99%
“…During primate evolution, the rate of Alu retrotransposition was 15-fold higher in human, chimpanzee and bonobo lineages than in gorilla and orangutan lineages 77 . Interestingly, LINE1 activity rates were suppressed in the human lineage compared with chimpanzee and bonobo lineages 77,78 , which may have resulted in a less diverse human population compared to non-human primate populations. By comparing human and non-human primate induced pluripotent stem cells (iPSCs), it was demonstrated that human iPSCs suppress LINE1 activity, as they have higher levels of Piwi-like protein 2 and APOBEC3B, which are known suppressors of LINE1 retrotransposition 78 .…”
Section: Box 1 | Evolutionary Impact Of Mobile Elementsmentioning
confidence: 99%
“…Cold (Hormozdiari et al 2013). The interspersed repetitive element content on the gorilla Y was different than that for gorilla autosomes (43.3%) and gorilla Chromosome X (52.2%).…”
Section: Repetitive Element Contentmentioning
confidence: 99%
“…Compared to the other two representative of Bovidae, the Tibetan antelope and sheep, BovB is more abundant in the Bovini genome (Table 2). It is known that LINEs can multiply with different success rates in different species (Hormozdiari et al, 2013) and a higher BovB activity could result in higher numbers of BOVA2 SINEs as seen in the lesser kudu genome.…”
Section: Bova2 and Bovb Expansion In The Lesser Kudu And Bovini Genomementioning
confidence: 99%